Finanšu pārskatu revīzijas nozīme uzņēmuma attīstībā - Griņevska, Inguna (Latvijas Universitāte, 2025)
Maģistra darba “Finanšu pārskatu revīzijas nozīme uzņēmuma attīstībā” mērķis ir izpētīt, kā finanšu pārskatu revīzija ietekmē mazo un vidējo uzņēmumu (MVU) finanšu datu ticamību un investīciju piesaisti Latvijā.

The aim of the Master’ s “The importance of Financial Statement auditing in development of a company” is to The aim of the master’s thesis is to investtigate how financial statement auditing affects the reliability of financial data of small and medium-sized enterprises(SMEs) and investment attraction in Latvia.
The importance of auditing financial statements in the development of a company
Keywords: Ekonomika un uzņēmējdarbība; finanšu pārskati; finanšu stabilitāte; revīzija; uzticamība; uzņēmuma attīstība